On the Learning of Languages by International and International Relations (Eurasian Journal of Learning and Academic Teaching, 2022)
In this article, by studying foreign languages, we will have the opportunity to get acquainted with the intellectual potential of young people around the world, exchange views with them, analyze the process in depth and compare our achievements and shortcomings with theirs. Their aspirations to learn foreign languages are described.